2019
DOI: 10.14720/aas.2019.114.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of planting dates on the growth and grain yield of two indigenous varieties of pearl millet (Pennisetum glaucum (L.) R.Br.) in a forest-savanna transition zone of Edo State, Nigeria

Abstract: Effects of planting dates on the growth and grain yield of two indigenous varieties of pearl millet (Pennisetum glaucum (L.) R.Br.) in a forest-savanna transition zone of Edo State, Nigeria Effects of planting dates on the growth and grain yield of two indigenous varieties of pearl millet (Pennisetum glaucum (L.) R.Br.) in a forest-savanna transition zone of Edo State, NigeriaAbstract: Effects of planting dates on the growth and grain yield of two indigenous varieties of pearl millet was carried out at the Tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 7 publications
2
20
1
Order By: Relevance
“…The sowing date significantly influences pearl millet performance [39,40]. The results from the grain yield dynamic analyses showed that Kantana, sown earlier by 14 January, had a yield advantage of up to 36% over Okashana-2; however, afterward, the yield dramatically decreased with subsequent delays in sowing (Table 3 and Figure 6).…”
Section: Crop Performancementioning
confidence: 99%
See 2 more Smart Citations
“…The sowing date significantly influences pearl millet performance [39,40]. The results from the grain yield dynamic analyses showed that Kantana, sown earlier by 14 January, had a yield advantage of up to 36% over Okashana-2; however, afterward, the yield dramatically decreased with subsequent delays in sowing (Table 3 and Figure 6).…”
Section: Crop Performancementioning
confidence: 99%
“…Various studies have shown that the growing season length and crop varieties of different maturity groups react differently to sowing dates. Studies by Nwajei et al (2019) and Nwajei (2023) demonstrated that pearl millet varieties respond differently to sowing dates, and the early-sown crop has higher nutrient uptake, growth, and grain yield than the late-sown one. So far, agronomic information elucidating the yield potential of traditional pearl millet varieties relative to their improved counterparts across the growing season has yet to be established for the NCR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results indicate that the yield of millet decreases when planting is delayed, suggesting an important role for timely planting in dealing with rainfall variability. Other studies have also shown that delayed planting of millet resulted in significant yield losses [13,32,33]. Farmers' evaluation of the experiments indicated that transplanting plays an important role for a better crop stand establishment (by reducing the need for replanting and gap filling) as well as for increasing yield.…”
Section: Farmers Perception Of Pearl Millet Transplantingmentioning
confidence: 99%
“…The onset of the rainy season is the most important driver of agricultural management [8,12]. It directly affects crop management practices, especially planting date, which has a significant effect on crop yield [13]. Given the unpredictability of the onset of the rainy season and subsequent individual rainfall events, as well as the large variability in total seasonal rainfall, agricultural production in the Sahel region of West Africa has become insufficient and uncertain to meet food security [14].…”
Section: Introductionmentioning
confidence: 99%